Cell Therapy for Treatment of Intervertebral Disc Degeneration: A Systematic Review. Issue 1 (May 2019) - Meisel, Hans-Joerg; Agarwal, Neha; Hsieh, Patrick C.; Skelly, Andrea; Park, Jong-Beom; Brodke, Darrel; Wang, Jeffrey C.; Yoon, S. Tim; Buser, Zorica
Study Design: Systematic review. Objective: To review, critically appraise, and synthesize evidence on use of cell therapy for intervertebral disc repair. Methods: A systematic search of PubMed/MEDLINE was conducted for literature published through October 31, 2018 and EMBASE andClinicalTrials.gov databases through April 13, 2018 comparing allogenic or autologous cell therapy for intervertebral disc (IVD) repair in the lumbar or cervical spine. In the absence of comparative studies, case series of ≥10 patients were considered. Results: From 1039 potentially relevant citations, 8 studies across 10 publications on IVD cell therapies in the lumbar spine met the inclusion criteria. All studies were small and primarily case series. For allogenic cell sources, no difference in function or pain between mesenchymal cell treatment and sham were reported in 1 small randomized controlled trial; 1 small case series reported improved function and pain relative to baseline but it was unclear if the change was clinically significant. Similarly for autologous cell sources, limited data across case series suggest pain and function may be improved relative to baseline; whether the changes were clinically significant was not clear. Safety data was sparse and poorly reported. The need for subsequent surgery was reported in 3 case-series studies ranging from 6% to 80%. Conclusions: The overall strength of evidence for efficacy and safety of cell therapy for lumbar IVD repair was very low primarily due to substantial risk of bias, small sample sizes and lack of a comparator intervention. Methodologically sound studies comparing cell therapies to other treatments are needed.